Characterization of microRNA profile in mammary tissue of dairy and beef breed heifers. (8th June 2015) - Wicik, Z.; Gajewska, M.; Majewska, A.; Walkiewicz, D.; Osińska, E.; Motyl, T.
Summary: MicroRNAs (miRNAs) are small non‐coding RNAs that participate in the regulation of gene expression. Their role during mammary gland development is still largely unknown. In this study, we performed a microarray analysis to identify miRNAs associated with high mammogenic potential of the bovine mammary gland. We identified 54 significantly differentially expressed miRNAs between the mammary tissue of dairy (Holstein‐Friesian, HF) and beef (Limousin, LM) postpubertal heifers. Fifty‐two miRNAs had higher expression in the mammary tissue of LM heifers. The expression of the top candidate miRNAs (bta‐miR‐10b, bta‐miR‐29b, bta‐miR‐101, bta‐miR‐375, bta‐miR‐2285t, bta‐miR‐146b, bta‐let7b, bta‐miR‐107, bta‐miR‐1434‐3p) identified in the microarray experiment was additionally evaluated by qPCR. Enrichment analyses for targeted genes revealed that the major differences between miRNA expression in the mammary gland of HF versus LM were associated with the regulation of signalling pathways that are crucial for mammary gland development, such as TGF‐beta, insulin, WNT and inflammatory pathways. Moreover, a number of genes potentially targeted by significantly differentially expressed miRNAs were associated with the activity of mammary stem cells. These data indicate that the high developmental potential of the mammary gland in dairy cattle, leading to high milk productivity, depends also on a specific miRNA expression pattern.